DROUGHT EVENTS, SPATIAL AND TEMPORAL VARIABILITY OF RAINFALL IN THE BRAZILIAN PANTANAL - Souza, Moisés Damasceno; Dallacort, Rivanildo; Silva, Dionei José Da; Dias, Vanessa Rakel de Moraes; Neves, Sandra Mara Alves da Silva; Oliveira, Gabriela Custodio (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
The Brazilian Pantanal is home to a rich biodiversity, regulating the hydrological cycle and providing inputs for the local economy. Spatial and temporal variation in precipitation influences the ecological dynamics of the biome, and drought, aggravated by decreased rainfall, impacts water resources and biodiversity. In this context, the objective of this work is to analyze the spatial and temporal distribution of rainfall and drought in the Brazilian Pantanal, between 1994 and 2023. Precipitation variability and the incidence of hydrological droughts in the Pantanal were estimated using ERA5-Land (?) data from 1994 to 2023, with global coverage and 9 km resolution. These data are continuous and without gaps, providing a complete global series for analysis. The standardized precipitation index (SPI) was used to monitor droughts, with negative values indicating water insufficiency and positive values indicating water surplus. In this study, SPI-3 and SPI-12 were quantified, used to monitor droughts considering 3 and 12 accumulated months, providing an analysis without space-time gaps, with observations in short and long periods. Annual precipitation in the Pantanal varied between less than 1000 mm and more than 2500 mm, with higher accumulations before the year 2000 and a reduction afterwards, especially in the last five years (2019-2023). The period from 1994 to 2001 had uniform rainfall of 1500 to 2500 mm, while subsequent years, such as 2002 and 2004, presented greater variations. The SPI identified different periods of precipitation anomalies, for SPI-3, the years with the greatest droughts, in terms of severity, intensity and duration, were 2019, 2020, 2021 and 2023. SPI-12 revealed alternating periods of drought and humidity in the last 30 years, with an increase in the frequency of dry events in recent years, indicating a downward trend.